Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Jimma University - International Livestock Research Institute; Jimma University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Jimma University. MOU signed on December 23, 2021 by Jimmy Smith, Director-General of ILRI and Jemal Abafita, President of Jimma University.